ANALISIS IMPLEMENTASI PROGRAM SAFE HOUSE 112 MITRA POLISI DI KOTA SALATIGA TAHUN 2013 - Amalia Purwatiningrum; Turtiantoro Turtiantoro; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
A sense of security is one of the things that humans need to support their dailyactivities. The police offered security through Program Safe House 112 wheresecurity is not only the police responsibility, but there is public participation in it.However, in the implementation of the Safe House program 112 is run into difficultybecause still rising crime that occurred in Salatiga. However, the formation of theProgram Safe House 112 does not have a considerable influence because it is stillrising crime that occurred in Salatiga.By this research, the writer wants to know the implementation of the ProgramSafe House 112 Police Partners and how far its impact on public order and securityenvironment in Salatiga. The writer limit discussion on the implementation scope ofcommunication, sources, and implementing attitude in the implementation ofProgram Safe House and factors which related with the impediment about ProgramSafe House 112 Police Partners in Salatiga.By using descriptive qualitative research methods and data collection byinterview and literature study, the writers found that the role of the Program SafeHouse 112 in minimizing rate crime can not be implemented to the fullest. Thewriters also found several factors that impede the implementation of the ProgramSafe House 112 Police Partners is socialization that takes a long time, a lack ofresources in fund, amount of program implementor, and lack of commitment andconsistensy in program implementing, as well as describe the conditions of securityand order situation in Salatiga.